Research hot topics and frontiers in social anxiety over the past decade: a CiteSpace bibliometric analysis based on Web of Science database from 2013 to 2023 - Zhang, Peng; Wang, Mingliang; Ding, Lin; Zhang, Jianing; Yuan, Yuqing; Tian, Xin (Frontiers in Psychiatry, 2024)
Objective To understand the current study of social anxiety (SA) over the past decade, and to analyze the research hot topics and frontiers in this field. Methods CiteSpace 6.2.R3 was used to analyze the literature on SA collected in the Web of Science Core Collection database from 2013 to 2023. Results A total of 9940 literature were included after the screening, and the annual publication volume showed a steady increase. The results emphasize that Zvolensky MJ, Pine DS, and Heimberg RG are important authors in the field of SA. The United States has the highest number of publications, with the University of California System contributing the most. Research hotspots include cognitive impairment, risk factors, complications, neuroimaging, and intervention strategies. SA related to the “theory of mind”, “bullying victimization”, “mobile phone”, “network analysis”, “technology”, and “satisfaction” are emerging research foci. Conclusion This study identifies the current situation and trends of SA research, and provides a reference for future research topics and directions.